2008
DOI: 10.1111/j.1532-849x.2007.00294.x
|View full text |Cite
|
Sign up to set email alerts
|

Shear Bond Strength between Feldspathic CAD/CAM Ceramic and Human Dentine for Two Adhesive Cements

Abstract: Within the assumptions and limitations of this study (including the small number of specimens) both bonding systems used achieved good shear bond strength values. The application of a silane coupling agent on the ceramic surface after etching with hydrofluoric acid increased the adhesion strength with both adhesive materials used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 30 publications
0
30
0
2
Order By: Relevance
“…found significantly higher bond strength when repairing porcelain with composite using two-bottle bis-silane, whereas one-bottle silane showed similar bond strength as the group without silane [38]. The adhesion between resin based cement and dentin seemed not to be compromised if the dentin was exposed to silane [39]. …”
Section: Discussionmentioning
confidence: 99%
“…found significantly higher bond strength when repairing porcelain with composite using two-bottle bis-silane, whereas one-bottle silane showed similar bond strength as the group without silane [38]. The adhesion between resin based cement and dentin seemed not to be compromised if the dentin was exposed to silane [39]. …”
Section: Discussionmentioning
confidence: 99%
“…The results of the present study were higher than their reports, and this may be regarded to use sandblasting and thermocycling in this study. It has been shown that sandblasting, etching and silane treatment may improve the bond strength significantly (6, 9, 10). The advantage of IPS Empress II is being reported as resistant to abrasion and good masking capability (11).…”
Section: Discussionmentioning
confidence: 99%
“…According to Graiff et al. , (9) there is a significant relation between cohesive failure and Excite/Variolink II systems. Altinas et al.…”
Section: Discussionmentioning
confidence: 99%
“…Graiff ve ark. 47 çalışmalarında, seramik yüzeyleri 110 µm boyutlarındaki alüminyum oksit partikülleri kullanarak pürüzlendirip, hidroflorik asit ile asitlemişlerdir. Daha sonra, bazı örnekler dual-polimerize yapıştırma simanı ile simante edilmiş, bazı numuneler ise silan kaplama ajanı uygulanıp dual-polimerize yapıştırma simanı ile simate edilmiştir.…”
Section: Dentine Bağlanmaunclassified